PENGARUH ECONOMIC VALUE ADDED, ARUS KAS OPERASI, RESIDUAL INCOME, EARNINGS, OPERATING LEVERAGE DAN MARKET VALUE ADDED TERHADAP RETURN SAHAM - ITA TRISNAWATI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2009)
This research is conducted to analyze the influence of Economic value added, cash flow from operations, residual income, earnings, operating leverage and Market value added to the stockholders’ return. This study was also intended to know which performances measures have the most significant effect to the return on shares. The samples of this research are consisting of 23 manufacturing companies that have been listed in the Jakarta’s Stock Exchange (JSX) for period 2003-2005 that has been selected by purposive sampling method. This study uses multiple regression method to see the contribution of each variable influence stockholders’ return. The empiric result indicates that all of the independent variables (Economic value added, cash flow from operations, residual income, earnings, operating leverage and Market value added) do not have significant influence to the return on shares.